2006
DOI: 10.1111/j.1365-2427.2006.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Hatching and viability of rotifer diapausing eggs collected from pond sediments

Abstract: 1. Planktonic rotifers inhabiting variable environments produce diapausing eggs that accumulate in the sediment of lakes and ponds, forming egg banks that may withstand adverse periods. A common assumption in zooplankton diapausing egg bank studies is to count as viable all eggs in the sediment that look healthy. This assumption should be challenged by asking how effectively 'healthy-looking' eggs represent viable eggs. 2. In this study, viability of more than 1100 'healthy-looking' diapausing eggs belonging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Given the low sedimentation rate of this lake, the deposition time of diapausing eggs spans over three decades, thus the large variation of hatching time we observed (between 4 and 7 days) may reflect differences in age of the eggs. Consistent with our results, viable zooplankton diapausing eggs are recorded in the upper 4-6 cm of sediments [49,92,[96][97][98][99][100][101]. Differences between environments can be related not only to differences in sedimentation rates but also to differences in the mortality rates of dormant stages, that can range between 1% y −1 and 64% y −1 [51,100,102,103].…”
Section: Discussionsupporting
confidence: 90%
“…Given the low sedimentation rate of this lake, the deposition time of diapausing eggs spans over three decades, thus the large variation of hatching time we observed (between 4 and 7 days) may reflect differences in age of the eggs. Consistent with our results, viable zooplankton diapausing eggs are recorded in the upper 4-6 cm of sediments [49,92,[96][97][98][99][100][101]. Differences between environments can be related not only to differences in sedimentation rates but also to differences in the mortality rates of dormant stages, that can range between 1% y −1 and 64% y −1 [51,100,102,103].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the uppermost 2 cm sediment has been indicated as active egg bank (Càceres & Hairston, 1998) and has been demonstrated that this portion obtains the highest success hatching in many zooplankton resting eggs, e.g. rotifer (Brachionus plicatilis complex species), cladocera and copepoda (Hairston et al, 1995;Cousyn & De Meester, 1998;Garcia-Roger et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Many zooplankton species are reported to be able to survive under adverse conditions through diapauses stage (e.g. Brendonck & De Meester, 2003;Gyllström & Hansson, 2004;Garcia-Roger et al, 2006). Analysis of resting egg banks has been considered as a useful technique to assess the diversity of zooplankton within a habitat (Brendonck & De Meester, 2003;Vandekerkhove et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One should check for neonates at least once per day for about two weeks. Viable resting eggs would usually hatch within one week of incubation (García-Roger et al, 2005;García-Roger et al, 2006;Walczyńska and Serra, 2014). During extended hatching trials one can transfer the eggs to new medium every 2-3 days in order to suppress fungal infections (García-Roger et al, 2005).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%